Case Report: Surgical Correction of a Cystic Duct Stump Leakage Following Cholecystectomy Using an Autologous Rectus Sheath Graft in a Dog - Han, Hyun-Jung; Kim, Kyu-Cahng; Yoon, Hun-Young (Frontiers in Veterinary Science, 2021)
A 2.7 kg, 13-year-old, castrated male Yorkshire Terrier was presented with bile peritonitis after cholecystectomy. Exploratory coeliotomy to identify and correct bile leakage revealed that the transected end of the cystic duct was open with no in-situ ligatures or vascular clips. The residual cystic duct stump was too short to ligate or seal directly. An autologous rectus sheath graft, harvested from the internal leaf of the rectus sheath, was used to patch the cystic duct stump. The graft was secured over the open duct using several simple interrupted sutures and covered with an omentalization. The clinical signs resolved after surgery, except for a transient increase in hepatobiliary enzyme levels and intrahepatic bile duct dilatation. The enzyme levels returned to near normal on day 25 after surgery. No intrahepatic bile duct dilatation was detected on day 55 after surgery. The owner was contacted for 3 years postoperatively and reported that the dog remained healthy without any long-term complications. Grafting using autologous rectus sheath can be used to treat cystic duct stump leakage that cannot be managed with direct closure using traditional modalities due to spatial constraints.